Minor differentiation despite high genetic diversity among closely related Hariana and Mewati cattle breeds from Northern India - B.Prakash; Deepika; Salar, Raj Kumar (Journal of Livestock Biodiversity, 2025)
Information on genetic organization and variability of livestock breeds is crucial for proficient conservation plans. The present investigation was undertaken to realize molecular characterization of closely related Hariana and Mewati cattle breeds from northern part of India on the basis of 21 FAO recommended microsatellite markers. Hariana breed has its native tract in the state of Haryana and Mewati inhabits adjoining areas of bordering states of Rajasthan and Uttar Pradesh. Both the breeds displayed high genetic diversity values. The average number of alleles per locus was 9.25 in Mewati and 11.81 in Hariana cattle. Gene diversity (expected heterozygosity) was very high and varied from 0.724 in Mewati to 0.777 in Hariana. Fis values were very low (almost zero) in both the breeds. Neighbour Joining radiation tree based on Nei’s genetic distance showed thorough admixture of animals of the two breeds. Only 0.56% variation was due to between breed differences and the remaining 99.44% due to individuals within breeds. PCA and AMOVA analysis revealed virtual absence of breed structure. High migration is the most probable factor for negligible differentiation between the two breeds. The study thus reveals extraordinarily low differentiation despite high genetic variability in the investigated breeds.